The relevance of hippocampal subfield integrity and clock drawing test performance for the diagnosis of Alzheimer’s disease and mild cognitive impairment - Hirjak, Dusan; Sambataro, Fabio; Remmele, Barbara; Kubera, Katharina Maria; Schröder, Johannes; Seidl, Ulrich; Thomann, Anne K.; Maier-Hein, Klaus H.; Wolf, Robert Christian; Thomann, Philipp (The world journal of biological psychiatry, 2019)
Objectives: The clock drawing test (CDT) is one of the worldwide most used screening tests for Alzheimer’s disease (AD). MRI studies have identified temporo-parietal regions being involved in CDT impairment. However, the contributions of specific hippocampal subfields and adjacent extrahippocampal structures to CDT performance in AD and mild cognitive impairment (MCI) have not been investigated so far. It is unclear whether morphological alterations or CDT score, or a combination of both, are able to predict AD. Methods: 38 AD patients, 38 MCI individuals and 31 healthy controls underwent neuropsychological assessment and MRI at 3 Tesla. FreeSurfer 5.3 was used to perform hippocampal parcellation. We used a collection of statistical methods to better understand the relationship between CDT and hippocampal formation. We also tested the clinical feasibility of this relationship when predicting AD. Results: Impaired CDT performance in AD was associated with widespread atrophy of the cornu ammonis, presubiculum, and subiculum, whereas MCI subjects showed CDT-related alterations of the CA4-dentate gyrus and subiculum. CDT correlates in AD and MCI showed regional and quantitative overlap. Importantly, CDT score was the best predictor of AD. Conclusions: Our findings lend support for an involvement of different hippocampal subfields in impaired CDT performance in AD and MCI. CDT seems to be more efficient than subfield imaging for predicting AD.
Gesehen am 15.11.2019
Published online: 31 Aug 2017